Phylogenomic Analyses and Reclassification of Species within the Genus Tsukamurella: Insights to Species Definition in the Post-genomic Era - Teng, Jade L. L.; Tang, Ying; Huang, Yi; Guo, Feng-Biao; Wei, Wen; Chen, Jonathan H. K.; Wong, Samson S. Y.; Lau, Susanna K. P.; Woo, Patrick C. Y. (Frontiers in Microbiology, 2016)
Owing to the highly similar phenotypic profiles, protein spectra and 16S rRNA gene sequences observed between three pairs of Tsukamurella species (Tsukamurella pulmonis/Tsukamurella spongiae, Tsukamurella tyrosinosolvens/Tsukamurella carboxydivorans and Tsukamurella pseudospumae/Tsukamurella sunchonensis), we hypothesize that and the six Tsukamurella species may have been misclassified and that there may only be three Tsukamurella species. In this study, we characterized the type strains of these six Tsukamurella species by tradition DNA-DNA hybridization (DDH) and “digital DDH” after genome sequencing to determine their exact taxonomic positions. Traditional DDH showed 81.2±0.6% to 99.7±1.0% DNA-DNA relatedness between the two Tsukamurella species in each of the three pairs, which was above the threshold for same species designation. “Digital DDH” based on Genome-To-Genome Distance Calculator (GGDC) and Average Nucleotide Identity (ANI) for the three pairs also showed similarity results in the range of 82.3-92.9% and 98.1-99.1% respectively, in line with results of traditional DDH. Based on these evidence and according to Rules 23a and 42 of the Bacteriological Code, we propose that T. spongiae Olson et al. 2007 should be reclassified as a later heterotypic synonym of T. pulmonis Yassin et al. 1996, T. carboxydivorans Park et al. 2009 as a later heterotypic synonym of T. tyrosinosolvens Yassin et al. 1997, and T. sunchonensis Seong et al. 2008 as a later heterotypic synonym of T. pseudospumae Nam et al. 2004. With the advancement of genome sequencing technologies, classification of bacterial species can be readily achieved by “digital DDH” than traditional DDH.